Gram-Negative Versus Gram-Positive (Actinomycete) Nonobligate Bacterial Predators of Bacteria in Soil - Zeph, Lawrence R. (1986)
The existence of nonobligate bacterial predators of bacteria in soil has been previously reported. Several additional predators were isolated from soil and tested for predation in situ in soil by use of the indirect bacteriophage analysis technique. The trials were conducted with nutritionally poor and nutritionally enriched soil. Certain of the predators that were gram negative were found to attack a range of both gram-positive and gram-negative host cell species, including at least some of the other predator bacteria, both gram positive and gram negative. The attack occurred in both the nutritionally poor and rich soils, but in some instances it was somewhat depressed in the rich soil. This may be due to the nonobligate nature of the predation. The gram-positive predators attacked a relatively narrow range of prey species, and the attack occurred only in the nutritionally rich soil. In addition, the gram-positive predators were subject to attack by certain of the gram-negative predators. These gram-negative predators therefore appeared to play a dominant role in the control of bacterial numbers in soil.